2018
DOI: 10.1007/s00221-018-5251-1
|View full text |Cite
|
Sign up to set email alerts
|

Task-relevant cognitive and motor functions are prioritized during prolonged speed–accuracy motor task performance

Abstract: This study aimed to explore the effect of prolonged speed-accuracy motor task on the indicators of psychological, cognitive, psychomotor and motor function. Ten young men aged 21.1 ± 1.0 years performed a fast- and accurate-reaching movement task and a control task. Both tasks were performed for 2 h. Despite decreased motivation, and increased perception of effort as well as subjective feeling of fatigue, speed-accuracy motor task performance improved during the whole period of task execution. After the motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…Specifically, the finding that initiation times became slower as a function of ToT suggests that the participants’ preparation of their visually guided movements was compromised by ToT. In line with Solianik et al’s (2018) study, there was also evidence for a faster, but not more accurate movement execution under fatigue. This finding cannot be unequivocally interpreted as impulsivity because there was no significant increase in error over time, and, therefore, it does not directly support Hypothesis 2.…”
Section: Methodssupporting
confidence: 64%
See 2 more Smart Citations
“…Specifically, the finding that initiation times became slower as a function of ToT suggests that the participants’ preparation of their visually guided movements was compromised by ToT. In line with Solianik et al’s (2018) study, there was also evidence for a faster, but not more accurate movement execution under fatigue. This finding cannot be unequivocally interpreted as impulsivity because there was no significant increase in error over time, and, therefore, it does not directly support Hypothesis 2.…”
Section: Methodssupporting
confidence: 64%
“…For example, Rozand et al (2015) found an increased movement duration in an arm-pointing task when it was performed after another cognitively fatiguing task. In contrast, the findings in Solianik et al’s (2018) study suggested that the execution of a reaching movement controlled by a handle towards a visual target was actually faster and less variable with increasing ToT (Solianik et al, 2018). The pointing task in the present set of studies was similar to that used by Solianik et al (2018) in terms of the quickly reachable targets presented on a screen.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…Evidence of an increase in MEP amplitude following an extended attention-demanding task was also supported by a more recent study focusing on cognitive changes due to prolonged motor actives. Solianik et al (2018) investigated changes to fNIRS-evoked cognitive activities and motor function following a 2 h speed-accuracy motor task compared with a non-demanding control task. Following the motor task, the authors noted increased prefrontal oxygenation (driven by decreased [HbR]) along with an increased resting MEP, whereas the non-demanding control task exhibited no changes on either cognitive biomarkers or cortical excitability.…”
Section: Relationship Between Cortical Excitability and Fnirs Measuresmentioning
confidence: 99%
“…“Go/NoGo” and “Stroop” test exercises are widely used for inducing cognitive fatigue ( Netz et al, 2016 ; Solianik et al, 2018 ). These and similar exercises usually last from 30 min to several hours and cause a decrease in mental working capacity ( Shigihara et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%